Master your motivation: A practical guide to unstick yourself, build momentum and sustain long-term motivation - Meurisse, Thibaut (New Delhi Wisdom tree, 2021)
Struggle to motivate yourself? Feel stuck, unable to complete your key tasks? Can't sustain motivation over the long-term? If so, it's time you make changes and get your motivation back. In author and coach, thibaut meurisse$1 (Bs latest book, you'll learn exactly how to rebuild your motivation and sustain it over the long-term. You$1 (Bll discover: the one thing you need to do right now to unstick yourself and get your motivation back how to declutter your mind and your environment to let your inner drive come back 25 simple yet powerful strategies to regain your motivation a simple method to boost your self-esteem and Turbochargers your motivation a powerful framework to build momentum and sustain motivation long-term, and much more.Master Your motivation is your must-read guide for regaining your motivation and living the life you want. If you like easy-to-understand strategies, practical exercises, and no-nonsense teachers, you'll love this book.s
Keywords: Motivation